Driving against the Power: Sexism in Automobile Culture and Female Drivers in Turkiye - S. Yetkin Işık; Birgül Koçak Öksev (Journal of Economy Culture and Society)
This article’s aim is to understand the socio-historical factors behind sexist judgments against female drivers in Turkey, based on written and visual media, social media content with the theme of “female driver errors,” and everyday male conversations in which being a woman is equated with novice driving. The article seeks to answer whether the increase in thenumber of female drivers is a symptom of a feminization of the driving profession and automobile culture. It is based on interviews with seventeen middle-class drivers (academic, teacher, doctor, psychologist), three of whom were men. In Turkey, the automobile is still an object with connotations of status, power, prestige, and competitiveness, and historically men have been dominant in automobile-related professions. Meanwhile, the normalization of women walking around the city without a man is a relatively new development for a significant part of society. The recent expansion of conservative and/or religious middle classes seems to support the increase in the number of female drivers. Automobile manufacturers’ market-expansion strategies and efforts to produce new models for each type of user also support this trend. However, production and sales strategies that try to catch up with the diversity of demand by considering the diversity of consumers are also effective in reproducing sexist stereotypes, such as some car models being labeled as “women’s cars”.